2009
DOI: 10.1269/jrr.08075
|View full text |Cite
|
Sign up to set email alerts
|

High LET Heavy Ion Radiation Induces p53-Independent Apoptosis

Abstract: Conventional clinical treatments with X-rays provide an effective modality for widely various human cancers, however, therapeutic results are sometimes poor. Many mutations have been reported to be in the p53 gene in advanced human cancers. The p53 plays a pivotal role in the pathway which controls apoptosis, cell growth and cell proliferation, and mutations or deletions in the p53 gene lead to resistance to cancer therapy. The involvement of the p53 gene in determining the sensitivity of many cell types towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 52 publications
3
33
1
Order By: Relevance
“…They have suggested that low-LET and high-LET radiation trigger different apoptotic pathways. While low-LET radiation mediated p53-induced caspase-8-dependent apoptosis, damage from high-LET radiation could induce mitochondria-dependent and p53-independent apoptosis through caspase-9 [29]. This result correlates with our data showing higher caspase-9 than caspase-8 activity in cells treated with combined metformin and neutron radiation.…”
Section: Discussionsupporting
confidence: 89%
“…They have suggested that low-LET and high-LET radiation trigger different apoptotic pathways. While low-LET radiation mediated p53-induced caspase-8-dependent apoptosis, damage from high-LET radiation could induce mitochondria-dependent and p53-independent apoptosis through caspase-9 [29]. This result correlates with our data showing higher caspase-9 than caspase-8 activity in cells treated with combined metformin and neutron radiation.…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, cell death induced by irradiation with carbon ions is independent of p53 [20]. Here we firstly observed that the radiosensitivity of GBM cells does not depend on p53 or MGMT status, whatever the type of irradiation, and secondly that the efficiency of carbon beam irradiation is about twofold higher than that of photons.…”
Section: Discussionmentioning
confidence: 55%
“…Another issue arises from the fact that most efficacy studies reported so far have utilized low linear energy transfer (LET) IR such as g rays and X-rays for irradiation. Future work will need to document the efficacy of selected agents against the damage produced by high LET particle radiations, since they are utilized in hadrontherapy, are major components of IR exposure from the detonation of nuclear devices and differ in some of their biological effects from low LET radiations [163]. Moreover, different agents appear to ameliorate only certain aspects of IR injury such that combining several compounds with distinct and complementary spectrum of activity may be required for optimal medical prevention or therapy of ARS.…”
Section: Expert Opinionmentioning
confidence: 99%